The Role of Myeloperoxidase in Biomolecule Modification, Chronic Inflammation, and Disease - Davies, Michael J; Hawkins, Clare L (Antioxidants & redox signaling, 2020)
The release of myeloperoxidase (MPO) by activated leukocytes is critical in innate immune responses. MPO produces hypochlorous acid (HOCl) and other strong oxidants, which kill bacteria and other invading pathogens. However, MPO also drives the development of numerous chronic inflammatory pathologies, including atherosclerosis, neurodegenerative disease, lung disease, arthritis, cancer, and kidney disease, which are globally responsible for significant patient mortality and morbidity. The development of imaging approaches to precisely identify the localization of MPO and the molecular targets of HOCl is an important advance, as typically the involvement of MPO in inflammatory disease has been inferred by its presence, together with the detection of biomarkers of HOCl, in biological fluids or diseased tissues. This will provide valuable information in regard to the cell types responsible for releasing MPO , together with new insight into potential therapeutic opportunities. Although there is little doubt as to the value of MPO inhibition as a protective strategy to mitigate tissue damage during chronic inflammation in experimental models, the impact of long-term inhibition of MPO as a therapeutic strategy for human disease remains uncertain, in light of the potential effects on innate immunity. The development of more targeted MPO inhibitors or a treatment regimen designed to reduce MPO-associated host tissue damage without compromising pathogen killing by the innate immune system is therefore an important future direction. Similarly, a partial MPO inhibition strategy may be sufficient to maintain adequate bacterial activity while decreasing the propagation of inflammatory pathologies.